Preparation Of Superhydrophobic Zinc Oxide Nanorods Coating On Stainless Steel Via Chemical Bath Deposition. (August 2019) - Nuruddin, Ahmad; Yuliarto, Brian; Kurniasih, Santi; Setiyanto, Henry; Ramelan, Aditianto
Abstract: The stearic acid modified zinc oxide nanorod surface was coated with a stainless steel substrate to improve the contact angle and the sliding angle. Facilitated through ZnO seeding on the substrate, the ZnO nanorod was deposited via chemical bath deposition at different precursor concentrations. The surface hydrophobicity was modified by varying concentrations of stearic acid at and submmersion time. The contact angle was investigated in relation to the surface microstructure and modification. Results indicate that the density of ZnO nanorods on the substrate surface and stearic acid coverage are prerequisites for improving surface hydrophobicity. Superhydrophobic properties with a contact angle of 162° was obtained for ZnO deposited with 35 mM zinc nitrate and submerged in 8 mM stearic acid for 36 h, which allowed 5 μL water droplets to slide at 3.8°.